2018
DOI: 10.7189/jogh.09.010502
|View full text |Cite
|
Sign up to set email alerts
|

Program evaluation of an ORS and zinc scale-up program in 8 Nigerian states

Abstract: Background In Nigeria, diarrhea is the second leading killer of children under five. Between 2012-2017, the Clinton Health Access Initiative, Inc. (CHAI) and the Government of Nigeria implemented a comprehensive program in eight states aimed at increasing the percentage of children under five with diarrhea who were treated with zinc and oral rehydration solution (ORS). The program addressed demand, supply, and policy barriers to ORS and zinc uptake through interventions in both public and private … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…11,45 Studies have also shown that improvements in ORS coverage can be driven by changes in government policies, media campaigns, and community culture and beliefs. 2,23,24 According to our results, Sierra Leone had some of the highest ORS coverage in western sub-Saharan Africa in 2017. Sierra Leone has previously been described as an example of how community mobilisation can promote access to and awareness of ORS, even after a devastating civil war.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…11,45 Studies have also shown that improvements in ORS coverage can be driven by changes in government policies, media campaigns, and community culture and beliefs. 2,23,24 According to our results, Sierra Leone had some of the highest ORS coverage in western sub-Saharan Africa in 2017. Sierra Leone has previously been described as an example of how community mobilisation can promote access to and awareness of ORS, even after a devastating civil war.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, policies related to diarrhoea treatment set at the national level do not affect all subnational areas equally, and interventions are often implemented at the subnational level, such as those currently done in Nigeria and India. 23,24 Local-level estimates of ORS and RHF coverage are thus needed to identify vulnerable subpopulations most in need of increased efforts to prevent child mortality. Yet, to our knowledge, no study has estimated ORS coverage subnationally across multiple regions or has used geospatial modelling techniques to estimate ORS coverage in locations with sparse data, and no study has compared ORS coverage to patterns in RHF coverage.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…The Clinton Health Access Initiative (CHAI) during 2012 to 2016 engaged with governments, heath care providers, and communities to improve diarrhea treatment in Kenya, Uganda and selected high-mortality states of India and Nigeria [15]. The CHAI program enhanced and scaled-up the DAZT program to the 22 districts in Gujarat and 39 districts of Uttar Pradesh, as well as the entire state of Madhya Pradesh.…”
mentioning
confidence: 99%
“…In the three African countries where the CHAI activities were implemented, ORS coverage at baseline ranged from 38% to 44% [15] but zinc use was negligible. The CHAI interventions included improving knowledge about appropriate treatment for caregivers via schools and community health workers and for providers via education and mentorship as well as drug detailing.…”
mentioning
confidence: 99%
“…Details on the survey design have been published elsewhere (22). Brie y, data were collected using populationbased household surveys among caregivers of children under ve and employing a random two-stage cluster sampling methodology.…”
Section: Study Setting and Data Descriptionmentioning
confidence: 99%